MEASURES TO IMPROVE THE BUSINESS ENVIRONMENT FOR SMALL BUSINESS IN REGIONS - Ataboyeva , Sevara (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This analysis examines comprehensive measures to improve the business environment for small enterprises in regional contexts, identifying regulatory simplification, financial access expansion, infrastructure development, business support services, and human capital enhancement as critical intervention areas based on international evidence.